HISTORY OF COLONIALISM IN AMERICA IN MAYA ANGELOU'S POEM "ON THE PULSE OF MORNING" - Anggraeny, Fanny (ReALL - Research on Applied Linguistics and Literature, 2024)
This study uses a postcolonialism approach, where concepts such as colonialism, postcolonialism, and hybridity are used to identify the problems contained in the poem On the Pulse of Morning by Maya Angelou. The purpose of this study is to understand the background of the creation of the poem On the Pulse of Morning and compare it with social events at that time. The main questions asked in this study are: 1) What social events occurred at that time that were the background to the creation of On the Pulse of Morning, 2) What social impacts emerged after the event, which prompted Maya Angelou to write the poem. This study used descriptive qualitative research with data collection technique researchers used observational method and literature study though literature and historical books, journal, and weblogs. The results of the study show that America has undergone many changes since it was free from European colonialism. Colonialism brought bad habits to the American people. The increasingly open views of the American people made them want changes for the better. This desire was voiced through one of Maya Angelou's literary works of poetry entitled On the Pulse of Morning. The conclusion of this study shows that this poem voices unity and togetherness as well as changes in American citizens against discrimination and injustice felt by black citizens in America. The results of this study are expected to be a reference for further research on postcolonialism with deeper analysis techniques and clearer explanations.